3D Multicamera Dental Cast Scanning System - Adaškevičius, R.; Vasiliauskas, A. (Elektronika ir Elektrotechnika, 2008)
A possibility of creating a high accuracy device that could automatically measure dental arches by scanning dental casts is presented. The original multicamera system using four firewire cameras and two laser modules is designed. System software uses acquired data for measurement of dental arches, to store dental cast models in 3D databases, to use model data for design of appliances. The 15 dental casts were scanned and measured to test the reliability of multicamera system, contrasting with manual measurement. This system is useful objective tool for medical tasks solution and further investigations are required in order to confirm effectiveness in orthodontic patients care. Ill. 4, bibl. 10 (in English; summaries in English, Russian and Lithuanian).